Countries of the French Western Africa at the beginning of the 21st century problems of the economic development. - Fírerová, Ivana; Adamcová, Lenka; Harmáček, Jaromír, 1981-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2008)
The first chapter talks about the events that took place in the French Western Africa in the second half of the 20th century. The second chapter describes all the economics at the beginning of the 21st century. Economics are described with the basic indicators and economic activities. The third chapter is about the obstacles to the economic development and the purpose of the last chapter is to show the progress achieved in case of the obstacles.
Vedoucí práce: Lenka Adamcová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2009
Rok obhajoby 2009
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses